Floral association of adult Cyclocephala tucumana Brethes and Cyclocephala melanocephala (Fabricius) with passion flowers (Passiflora edulis Sims) - Dias, Bruno Mateus Ribeiro; Rodrigues, Sérgio Roberto (EntomoBrasilis, 2018)
Abstract. Adults of Cyclocephala tucumana Brethes and Cyclocephala melanocephala (Fabricius) were sampled in yellow passionflower flowers, being the first record of C. tucumana associated with flowers of this plant. Associação floral de adultos de Cyclocephala tucumana Brethes e Cyclocephala melanocephala (Fabricius) com flores de maracujá (Passiflora edulis Sims) Resumo. Adultos de Cyclocephala tucumana Brethes e Cyclocephala melanocephala (Fabricius) foram amostrados em flores de maracujá amarelo, sendo o primeiro registro de C. tucumana associada com flores dessa planta.